LESSONS FOR CONTEMPORARY YOUTH FROM THE WORKS OF ALEXANDER FEINBERG - Mamatova Dilnavo Sayqan qizi; Bazarov Ixtiyor (TADQIQOTLAR, 2026)
Abstract. This article explores the essence of Aleksandr Feinberg’s creative work and its significance in educating today’s youth. It analyzes key themes reflected in the poet’s works, such as humanity, patriotism, kindness, and the appreciation of life’s beauty. Furthermore, the article discusses the impact of Feinberg’s legacy on the spiritual development of the younger generation and the profound life lessons his poetry imparts.